(untitled) (Voices of Teachers and Teacher Educators, 2024)
Voices of Teachers and Teacher Educators (VTTE), an initiative of the Ministry of Education, erstwhile Ministry of Human Resource Development (MHRD), is a peer-reviewed e-journal coordinated by the NCERT. The journal is published biannually and is bilingual (Hindi and English). The journal highlights the vital role of teacher education in India, as the country is poised to provide quality education to all its children, irrespective of gender, caste, creed, religion, and geography. The National Curriculum Framework (NCF)-2005, National Curriculum Framework for Teacher Education (NCFTE)-2009, Right of Children to Free and Compulsory Education Act (RTE)-2009, and National Education Policy (NEP)-2020—all reflect this commitment, underline the principles that make such an effort necessary, as well as spell out the strategies for it. In this regard, we are faced with challenges that include augmenting the role of teachers in shaping the social transformation that India is witnessing, making education equitable, and effecting a long-lasting impact on the quality of education. Teachers and everyone concerned with education need to recognize that their ownership and voices are important and that they can and do learn not only from their own experiences but also from each other through collective reflection and analysis. The journal attempts to lend voice to students, teachers, teacher educators, researchers, administrators, and policymakers in varied institutions such as schools, Cluster Resource Centres (CRCs), Block Resource Centres (BRCs), District Institutes of Education and Training (DIETs), Institutes of Advanced Studies in Education (IASEs), Colleges of Teacher Education (CTEs), State Councils of Educational Research and Training (SCERTs), etc., as well as other stakeholders. The journal aims to facilitate the dissemination of their ideas and make their engagement visible in accomplishing the extraordinarily complex and diverse tasks that they are expected to perform. Contributions to the journal are welcome in both English and Hindi. Voices is published online, and we hope to circulate it widely. The journal seeks to provide a platform and build a network for our voices, ideas, and reflections; it carries articles, research papers, critical reviews, and book reviews and covers several themes in school and teacher education, including best practices, innovations, experiments, and action research. We look forward to suggestions and comments of our readers on the articles published. The views expressed and the information given in this journal are those of the authors and may not reflect the views of the NCERT.